Mycobacterium tuberculosis Rv0790c inhibits the cellular autophagy at its early stage and facilitates mycobacterial survival - Fang, Jun; Dong, Chunsheng; Xiong, Sidong (Frontiers in Cellular and Infection Microbiology, 2022)
Rv0790c is predicted to be a conserved hypothetical protein encoded by Mycobacterium tuberculosis (Mtb). However, its function in Mtb infection remains largely unknown. In this study, we found that Rv0790c promoted bacillary survival of M. smegmatis (Ms), both in vitro and in vivo. The bacillary burden of Ms exogenously expressing Rv0790c increased, whereas in Rv0790c-knockouts the bacillary burden decreased in infected macrophages. Multiple cellular processes were analyzed to explore the underlying mechanisms. We found that neither inflammatory regulation nor apoptotic induction were responsible for the promotion of bacillary survival mediated by Rv0790c. Interestingly, we found that Rv0790c facilitates mycobacterial survival through cellular autophagy at its early stage. Immunoprecipitation assay of autophagy initiation-related proteins indicated that Rv0790c interacted with mTOR and enhanced its activity, as evidenced by the increased phosphorylation level of mTOR downstream substrates, ULK-1, at Ser757 and P70S6K, at Thr389. Our study uncovers a novel autophagy suppressor encoded by mycobacterial Rv0790c, which inhibits the early stage of cellular autophagy induction upon Mtb infection and takes an important role in maintaining intracellular mycobacterial survival. It may aid in understanding the mechanism of Mtb evasion of host cellular degradation, as well as hold the potential to develop new targets for the prevention and treatment of tuberculosis.